FEMINIST LEADERSHIP FOUND ON QUEEN INGRITH IN “ MALEFICENT : MISTRESS OF EVIL”FILM - Meo, Maria Y; Wanggai, Febe F I; Liru, Marianus W (Lantern: Journal of Language and Literature, 2023)
The aims of this study were to find the elements of feminist leadership and how the influence effects of feminist leadership that arise in the development of Queen Ingrith's character in the film "Maleficent : Mistress of Evil" directed by Joachim Rønning. This study used descriptive qualitative method. The data was taken from the film Maleficent : Mistress of Evil in the form of words, phrases, utterances, conversation and action. The approach used was feminism because this study related to feminism values.The result of this study shows that there are four elements of feminist leadership and four influence effects that arise from Queen Ingrith’s character in this film. The first are elements of feminist leadership which include power, principles and values, politics and purpose, and the last is practice. The second is the influence effect that emerges from Queen Ingrith's character, namely, influence suits our leadership style, influence can be actively cultivated, influence is a tool for the times,and influence creates a new way to work. From the data above, it could be concluded that Queen Ingrith has two sides of leadership,namely female leadership and male leadership.